Gender Beliefs and Action Tendencies for Women’s Rights: Impact of National vis-à-vis International Policy Recommendations - Anjum , Gulnaz; Aziz, Mudassar; Chilton, Adam; Usman, Zahid (Journal of Development Policy Research and Practice (JoDPRP), 2017)
In most democratic developing countries, including Pakistan, a crucial and still least prioritised domain is reforms in the status of women’s rights. As reflected in the rankings provided by The Gender Gap Index Report (World Economic Forum 2016), Pakistan stands second from the bottom among 144 countries. There are many organisations and programmes at the international and national level that are trying to influence the challenged countries to improve women’s rights policies and practices including the United Nations’ Convention on the Elimination of all forms of Discrimination Against Women (CEDAW); Pakistan’s commitment to meeting the 17 Sustainable Development Goals (SDGs); and, the National Commission on the Status of Women (NCSW). The impact of national and international endorsement of the policies intended to improve women’s rights in Pakistan was explored in this survey. The survey was designed to see under which conditions, respondents would support policies focusing on women’s rights. The two conditions in the experiment were framed as such that the proposed reforms came from the National Government (national condition) or by the United Nations (international condition). As a comparative baseline, a control condition was added in which the source of proposals was not mentioned (control condition). The survey was conducted with 619 university students (males: 51%; females: 49 %). Data was collected from the students of the Quaid-i-Azam University, Islamabad; and, the Pakistan Institute of Development Economics, Islamabad, from March through August 2016. Results of the study indicated that compared to the control condition, the respondents in the national and international condition expressed higher support for policy reforms for women’s rights. Furthermore, participants in the national and international condition were more likely to offer help in the implementation of these policy reforms. At the policy level, the survey supported the claim that national level endorsement of the reforms, compared to the United Nations endorsement, makes propagation and acceptance of the women’s rights reforms easier for the general public. The scope of this article is related to the following SDG / SDGs.